Tissue-specific exposure of chromatin structure at the 5' terminus of the rat preproinsulin II gene. - Wu, C (1981)
The 5' terminus of the rat preproinsulin II gene exhibits a tissue-dependent DNase I sensitivity. Only in the chromatin froma pancreatic beta-cell tumor, but not in liver, spleen, kidney, or brain chromatin, is a region at and before the 5' end of the gene exposed to cleavage. The region of exposure extends 250-300 base pairs upstream from the 5' terminus of the preproinsulin mRNA. Such a region may allow control sequences special access to regulatory proteins.